Pengenalan Simplisia dan Pelatihan Pembuatan Teh Celup Telang dan Bawang Dayak Bagi Kader Puskesmas Mataraman - Sari, Okta; Setiawan, Deni; Putra, Aditya Maulana Perdana; Wathan, Nashrul; Mardiati, Nurul; Lingga, Herningtyas Nautika; Akbar, Nabila Hadiah (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2024)
Using traditional medicinal plants to create health products like herbal medicines and tea bags is one way to improve health. Telang (Clitoria ternatea) and Dayak Onion (Eleutherine bulbosa) are two types of plants that have great potential in the world of health, but their use has not been optimal. The purpose of this service is to improve the knowledge of Mataraman Health Centre cadres in the processing of herbal medicines and the utilisation of TOGA. At the Mataraman Health Center, community service has been conducted. The implementation of activities aimed at providing education on the introduction of herbal medicines using leaflets. Training is being conducted to process dry herbal medicines, utilize medicinal plants, and create tea bags. Evaluation of activities is carried out through pretests and posttests. A total of 10 cadres from Mataraman Health Centre participated in this activity. After receiving the education, the average level of knowledge among the participants increased to 84%. The use of herbal plants as herbal medicines can inspire the community to develop and preserve the potential of traditional medicinal plants. We hope that this activity will serve as a foundational step, providing cadres with valuable insights to develop herbal medicines.